Direct and Indirect Effects of Conflicts, Violence and War on Economic Growth in Sri Lanka - Santhirasekaram, S.; Amirthalingam, Kopalapillai (My University, 2010)
This study shows that the ethnic conflict, violence and war between and within communities have adversely affected the economic growth in Sri Lanka during 1960-2005 period. The thrust of this study is to show the various adverse impacts of conflicts and war on economic growth. Empirical findings based on Ordinary Least Squares (OLS) estimation using time series data collected from various annual reports of Sri Lanka used in this study shows that conflict, violence and war, measured by a proxy measure of annual growth rate of tourist arrivals, scaled from zero (peace) to ten (conflict, violence and war) scores, negatively and significantly affects the economic growth. Sri Lanka has lost an average of 2.53 per cent annual growth rate due to the direct effect of conflict, violence and war. Due to indirect effects of conflict, violence and war, the country has lost an average of 1.03 per cent and 1.5 per cent annual growth by the way of reduced physical capital accumulation and reduced human capital accumulation respectively. If Sri Lanka had not had conflicts and war, it would have achieved an average of 10.06 per cent growth during 1978-2005 period. Though Sri Lanka achieved moderate growth during war time, inflation, lose of external value of rupee, increased public debt etc. had been impediments to achieving other macroeconomic objectives.
Keywords: Peace; conflicts; violence; war; socio-political instability; economic growth